Impact of Coal Washing Activities on Water Quality and The Community of Aquatic Life In The Barito River, South Barito Regency - Lovina Gianina; Ipung Fitri Purwanti (International Journal of Science and Environment (IJSE), 2025)
The Barito River is a recipient of pollution from various human activities such as agriculture, settlements, and especially the mining industry. Coal washing activities along the Barito River Basin (DAS) are one of the activities that have the most significant impact on water quality degradation. This research aims to analyze the impact of coal washing activities on water quality and aquatic biota communities in the Barito River, South Barito Regency. The research location is the Barito River, South Barito Regency. Sampling points were taken at three points: upstream, outfall, and downstream of the Barito River. Water quality parameters in the Barito River include physical aspects (temperature and TSS), chemical (DO, pH, Fe, and Mn), and biological (nekton, plankton, and benthos) measured using the SNI method and specific fishing gear. Water quality assessment was carried out using the Storet method and the Pollution Index (IP) to determine water quality status based on parameters that do not meet quality standards. The water quality of the Barito River is classified as lightly to moderately polluted. Most physicochemical parameters are still within quality standards, except for low DO and Mn at several points exceeding the threshold. Storet results showed a score of -10 (class B, light pollution), while the Pollution Index (IP) was 1.98 (light pollution). Coal washing activities affected the distribution of aquatic biota. The diversity index (H’) of nekton was moderate-high (2.64–3.17), plankton was moderate (1.70–2.06), and benthos was low (0.64–0.69). High evenness and low dominance values ​​indicated a relatively stable community, despite anthropogenic pressures. The presence of bioindicators such as Rasbora caudimaculata, Macrobrachium rosenbergii, and Bithynia sp. confirmed the influence of human activities on the ecosystem.